2016
DOI: 10.22424/jmsb.2016.34.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Crude Extracts of Kaempferia parviflora (Krachaidam) against Cronobacter spp. and Enterohemorrhagic Escherichia coli (EHEC) in Various Dairy Foods: A Preliminary Study

Abstract: Rhizomes of Kaempferia parviflora (Zingiberaceae) have been used in traditional Thai medicine for health promotion. In this study, the antibacterial activity of ethanol extract of K. parviflora against Cronobacter spp. and enterohemorrhagic Escherichia coli (EHEC) was investigated using paper disc dilution method. The results revealed that the ethanol extract exhibited antibacterial activity against Cronobacter spp. and EHEC. With an increasing concentration of K. parviflora ethanol extract, larger zones of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Consequently, the application of antibacterial substances derived from natural sources has received considerable attention. Previous research indicated that an ethanolic KP extract could inhibit growth of the bacteria Staphylococcus aureus [ 4 ] and Escherichia coli [ 26 ], which are responsible for skin infections. In this study, electrospun shellac fibers containing KP extract were tested for antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the application of antibacterial substances derived from natural sources has received considerable attention. Previous research indicated that an ethanolic KP extract could inhibit growth of the bacteria Staphylococcus aureus [ 4 ] and Escherichia coli [ 26 ], which are responsible for skin infections. In this study, electrospun shellac fibers containing KP extract were tested for antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Methoxyflavone was identified as an active component in the KP rhizome with a variety of biological properties, while KP activities include the support of sexual performance and antioxidant, antitumor growth and metastasis, bactericidal and anti-inflammatory effects [20][21][22][23][24]. The ethanol extract of KP inhibits Cronobacter spp., enterohemorrhagic Escherichia coli and H. pylori growth, which are offensive gastro-enteric pathogens [25]. In a previous study, the crude ethyl acetate extract of KP (CEAE-KP) was shown to reduce H. pylori pathogenic function by inhibiting their internalization process in human laryngeal carcinoma cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Kaempferia parviflora is one such medicinal plant of zingiberaceae whose rhizomes have been used as a remedy for many ailments by the native people of Manipur, North-East, India since time immemorial without proper scientific formulations. 8 The plant is locally known as Singmu in Manipuri and Thai ginseng or Black Ginger in Thailand. 9 Medicines derived from the rhizomes of Kaempferia parviflora have been reported to use for inflammation, hypertension, erectile dysfunction and abdominal ailments in Thai and Laos.…”
Section: Introductionmentioning
confidence: 99%
“…15 Also, a study reported that the plant possesses anti-plasmodial, antifungal and antibacterial activities. 8 In general, plant extract is considered to be the rich resource for isolating pharmacologically important natural products. 16 The phytoconstituent present in the plant extract vary significantly depending on the extraction method as well as polarity of the solvent used for extraction.…”
Section: Introductionmentioning
confidence: 99%